Protective effects and possible mechanisms of catalpol against diabetic nephropathy in animal models: a systematic review and meta-analysis - Fu, Zhongmei; Su, Xiaojuan; Zhou, Qi; Feng, Haoyue; Ding, Rui; Ye, Hejiang (Frontiers in Pharmacology, 2023)
Rehmannia glutinosa is a core Chinese herbal medicine for the treatment of diabetes and diabetic nephropathy (DN). It has been used for the treatment of diabetes for over 1000 years. Catalpol is the main active compound in Rehmannia roots. Current evidence suggests that catalpol exhibits significant anti-diabetic bioactivity, and thus it has attracted increasing research attention for its potential use in treating DN. However, no studies have systematically evaluated these effects, and its mechanism of action remains unclear. This study aimed to evaluate the effects of catalpol on DN, as well as to summarize its possible mechanisms of action, in DN animal models.We included all DN-related animal studies with catalpol intervention. These studies were retrieved by searching eight databases from their dates of inception to July 2022. In addition, we evaluated the methodological quality of the included studies using the SYstematic Review Center for Laboratory animal Experimentation (SYRCLE) risk-of-bias tool. Furthermore, we calculated the weighted standard mean difference (SMD) with 95% confidence interval (CI) using the Review Manager 5.3 software and evaluated publication bias using the Stata (12.0) software. A total of 100 studies were retrieved, of which 12 that included 231 animals were finally included in this review. Results: As compared to the control treatment, treatment with catalpol significantly improved renal function in DN animal models by restoring serum creatinine(Scr) 批注 [Fz1]: In the abstract, under Aim of the study section, diabetic nephropathy should be written as DN when it appears earlier.(p=0.0009) and blood urea nitrogen(BUN) (p<0.00001) levels, reducing proteinuria(p<0.00001) and fasting blood glucose(FBG) (p<0.0001), improving kidney indices(p<0.0001), and alleviating renal pathological changes in the animal models. In addition, it may elicit its effects by reducing inflammation and oxidative stress, improving podocyte apoptosis, regulating lipid metabolism, delaying renal fibrosis, and enhancing autophagy. Conclusions: The preliminary findings of this preclinical systematic review suggest that catalpol elicits significant protective effects against hyperglycemia-induced kidney injury. However, more high-quality studies need to be carried out in the future to overcome the methodological shortcomings identified in this review.